Factors Explaining the Risk Attitude towards Entrepreneurship in Pakistan: An Exploratory Analysis (The Pakistan Development Review, 2016)
This study empirically identifies factors which explain the attitude of individuals towards entrepreneurship, and how attitudes toward risk influence the likelihood of a person turning entrepreneur. The variable ‗fear of failing‘ serves as a proxy variable reflecting risk aversion, as contained in the dataset compiled by the Global Entrepreneurship Monitor (GEM), through interviews of a sample of 2,007 respondents from Pakistan, in 2010. Given that the dependent variable is of binary nature, the probit model is used to empirically determine as to how various demographic, and perceptual factors influence risk aversion among the country‘s citizens, particularly in the context of starting their own businesses. The results suggest that personally knowing other entrepreneurs, who have launched a business in the past two years is the most significant variable affecting risk attitudes among Pakistanis; specifically, those who personally know entrepreneurs are more likely to have a fear of failure, with marginal effects as high as 8 percent. Meanwhile, individuals who feel that society generally approves of entrepreneurship as a career choice are around 5 percent less likely to fear failure, though this is a weak correlation. A number of other variables—which are reported in the literature to have significant correlation with risk attitudes in a global context—are not found to be correlated at traditional significance level for Pakistan. In addition, the study does not reveal systematic differences in the risk attitude of individuals hailing from urban and rural areas, or at provincial level. We suggest some preliminary implications based on the findings, and also identify a potential avenue for follow-up research. JEL Classification: L26; M13; O53 Keywords: Entrepreneurship; Emerging Economy; Risk Aversion